Sustainable Valorization of Salak Peel Waste: Regeneration of Biochar for Lead Removal from Wastewater - Buakhiao, Phruektinai; Chungcharoen, Thatchapol; Jamkamon, Aud; Limmun, Warunee; Thungsotanon, Dithaporn (My University, 2026)
This study evaluates the effects of pyrolysis temperature (600°C and 800°C, denoted as SP600 and SP800) and regeneration reagents on lead (Pb²⁺) adsorption performance of biochar derived from salak peels. Moreover, the lead removal efficiency and adsorption efficiency after several regeneration cycles under appropriate conditions were also investigated. The results indicate that increasing the pyrolysis temperature significantly enhances lead removal efficiency and adsorption capacity, with biochar pyrolyzed at 800°C and loaded with lead (SP800Pb) exhibiting the highest initial lead adsorption performance. However, upon regeneration using hydrochloric acid (HCl) and sodium nitrate (NaNO₃) at various concentrations, SP600Pb demonstrated higher lead removal performance than SP800Pb across all conditions. Specifically, SP600Pb regenerated by 0.1M HCl exhibited the highest lead desorption efficiency and removal efficiency. Furthermore, after five consecutive adsorption-regeneration cycles, the biochar regenerated by 0.1M HCl (SP600RPb) exhibited a suitable removal efficiency of 83.91 ± 0.10 and a desorption efficiency of 148.73 ± 0.13. The observed desorption efficiency exceeding 100 was attributed to the accumulated release of Pb²⁺ ions during successive regeneration cycles, which indicates enhanced ion-exchange dynamics over time. Therefore, biochar pyrolyzed at 600°C and regenerated using 0.1M HCl is appropriate for the reuse of biochar in lead adsorption, promoting sustainable resource application, cost reduction, and waste minimization in production processes.
Keywords: biochar regeneration; biomass; circular economy; ecological adsorbent; lead adsorption; salak peels; Sustainable Development Goals SDGs